White Columns Update 1988-1989. (New York : White Columns, 1989)
Albertini, Bill ; McClennan, Peter ; Reynolds, Hunter ; Weinman, Judith ; Jenkins, Michael ; Bramlette, Teresa ; Andrews, Jonathan ; Nash, Laura ; Sugiura, Kunié ; Fromme, Julie ; etc.
White Columns Update 1988-1989, White Columns, New York, October 6 - November 5, 1989
boek